Application of differential scanning calorimetry in hair samples as a possible tool in Forensic Science - Ionashiro, Elisa Yuki; Hewer, Thiago Lewis Reis; Fertonani, Fernando Luis; de Almeida, Eduardo Tonon; Ionashiro, Massao (Eclética Química, 2004)
The Differential Scanning Calorimetry (DSC) was used to study the thermal behavior of hair samples and to verify the possibility of identifying an individual based on DSC curves from a data bank. Hair samples of students and officials from Instituto de Química de Araraquara, UNESP were obtained to build up a data bank. Thus to sought an individual, under incognito participant of this data bank, was identified using DSC curves.